2023
DOI: 10.1021/jacs.3c06622
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Specification of E3 Ubiquitin Ligase Engagement by Cysteine-Reactive Chemistry

Roman C. Sarott,
Inchul You,
Yen-Der Li
et al.

Abstract: Targeted protein degradation relies on small molecules that induce new protein–protein interactions between targets and the cellular protein degradation machinery. Most of these small molecules feature specific ligands for ubiquitin ligases. Recently, the attachment of cysteine-reactive chemical groups to pre-existing small molecule inhibitors has been shown to drive specific target degradation. We demonstrate here that different cysteine-reactive groups can specify target degradation via distinct ubiquitin li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
(55 reference statements)
2
11
0
Order By: Relevance
“…We show that our previously discovered covalent BRD4 degrader bearing a “fumarate” handle acts through RNF126, and not through DCAF16. Our results are analogous to recent findings with covalent heterobifunctional BRD4 degraders bearing two different electrophilic handles that act through DCAF16 and DCAF11 18 . Our study also suggests that pre-existing weak interactions between the E3 ligase and protein target may not be necessary to develop monovalent degraders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We show that our previously discovered covalent BRD4 degrader bearing a “fumarate” handle acts through RNF126, and not through DCAF16. Our results are analogous to recent findings with covalent heterobifunctional BRD4 degraders bearing two different electrophilic handles that act through DCAF16 and DCAF11 18 . Our study also suggests that pre-existing weak interactions between the E3 ligase and protein target may not be necessary to develop monovalent degraders.…”
Section: Discussionsupporting
confidence: 91%
“…Given that several previous studies have identified DCAF16 as the E3 ligase substrate receptor responsible for the degradation of covalent BRD4 degraders bearing various different types of electrophilic handles, in part because of the native weak affinity between BRD4 and DCAF16 13,18,26,27 , we next determined whether our previously discovered covalent monovalent BRD4 degrader, JP-2-197, bearing a but-2-ene, 1,4-dione “fumarate” covalent degrader handle that targets RNF126 instead acts through DCAF16 25 . We showed that the BRD4 degradation observed by JP-2-197 was not mitigated at all in DCAF16 knockout cells (Figure 4a-4b) .…”
Section: Resultsmentioning
confidence: 99%
“…We showed that alkenyl oxindoles can recruit DCAF11, thus acting as a novel PROTAC moiety for targeted protein degradation. Previously, the Cravatt 37 and Gray 38 groups respectively revealed that DCAF11 serves as an E3 ligase that can support protein degradation triggered by electrophilic PROTACs. As alkenyl oxindole possesses Michael acceptor properties, we hypothesize that it recruits DCAF11 through a covalent modification approach, potentially engaging with cysteine residues.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, unbiased de novo design of molecular glue degraders remains challenging and derivatization of known E3 ligase engaging compounds has proven to be a more effective molecular glue discovery strategy. [5][6][7] Cereblon (CRBN), a substrate receptor of the CUL4-RBX1-DDB1-CRBN (CRL4 CRBN ) ubiquitin E3 ligase, is the target of glutarimide-containing chemical ligands. Chemical derivatization of the glutarimide scaffold is an established strategy for expansion of the CRBN molecular glue target space.…”
Section: Introductionmentioning
confidence: 99%